2023
DOI: 10.3390/cancers15123169
|View full text |Cite
|
Sign up to set email alerts
|

CAR-NK Cells Targeting HER1 (EGFR) Show Efficient Anti-Tumor Activity against Head and Neck Squamous Cell Carcinoma (HNSCC)

Abstract: (1) Background: HNSCC is a highly heterogeneous and relapse-prone form of cancer. We aimed to expand the immunological tool kit against HNSCC by conducting a functional screen to generate chimeric antigen receptor (CAR)-NK-92 cells that target HER1/epidermal growth factor receptor (EGFR). (2) Methods: Selected CAR-NK-92 cell candidates were tested for enhanced reduction of target cells, CD107a expression and IFNγ secretion in different co-culture models. For representative HNSCC models, patient-derived primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Target cell killing by NK cells is well known to be vetoed by signals of inhibitory receptors and NK cells could be effective as CAR transduced effector cells for off-the-shelf cancer immunotherapy. 77 Importantly, Cho and colleagues demonstrated that an inhibitory zipCAR that failed to reduce cytotoxic activity of CD8 T cells was efficient in NK cells. 35 The inhibitory zipCAR used in their study also harbored an intracellular domain derived from BTLA, suggesting differential effects of inhibitory signaling in these cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Target cell killing by NK cells is well known to be vetoed by signals of inhibitory receptors and NK cells could be effective as CAR transduced effector cells for off-the-shelf cancer immunotherapy. 77 Importantly, Cho and colleagues demonstrated that an inhibitory zipCAR that failed to reduce cytotoxic activity of CD8 T cells was efficient in NK cells. 35 The inhibitory zipCAR used in their study also harbored an intracellular domain derived from BTLA, suggesting differential effects of inhibitory signaling in these cell types.…”
Section: Discussionmentioning
confidence: 99%
“…CSCs express TAAs common to tumor cells that their targeting resulted in transient responses. [68] The heterogeneity of CSC antigens could also be improved by using CARs targeting multiple CSC antigens, [69] using dual-specific CAR-T cells, [70] and using combination therapy to enhance the antitumor efficacy of CAR-T cells and overcome the shortcomings of CAR-T cell monotherapy. [71] The trafficking, persistence, and penetration of CAR-NK/T cells in solid tumors could be enhanced by developing CAR-T cells expressing chemokine receptors (such as CCL19, CCR4, CXCR2, and CCR2b) and extracellular matrix (ECM)-degrading enzymes (such as heparanase), using armored CAR-T cells to overcome immunosuppressive immune cells, inducing memory properties, and combining with oncolytic virotherapy.…”
Section: Engineered Immune Cells Targeting Cscspecific Antigensmentioning
confidence: 99%